Hey there! Welcome to Brainly! I'm happy to help you!
Let's quickly write our equation below.
4(1-x)+2x=-3(x+1)
To solve this, we want to get the x by itself on one side of the equation so we can see what it equals on the other side. First, we need to get it out of the parentheses. To do this, we will use the <em><u>distributive property </u></em>and multiply the number before the parentheses by both terms inside of it as seen below! :)
4(1)-4(x)+2x=-3(x)-3(1)
4-4x+2x=-3x-3
Now, we need to combine our like terms.
4-2x=-3x-3
Now, we want to get all of our constants (numbers without variables) onto the right side. First, we will subtract four from both sides.
-2x=-3x-7
Now, we will add 3x to both sides.
x= -7
I hope that this helps! Have a wonderful day!